Genome cloning and genetic evolution analysis of eight duck-sourced novel goose parvovirus strains in China in 2023 - Zhan, Guangjian; Liu, Nan; Fan, Xiaole; Jiang, Wansi; Yuan, Mengxue; Liu, Yunwang; Dong, Shishan (Frontiers in Microbiology, 2024)
To clarify the biological characteristics and genetic evolution of novel goose parvovirus (NGPV), ducks with short beaks and dwarfism syndrome from Shandong and Henan Province were investigated by dissection and the tissue samples were collected for study. Eight strains of NGPV were isolated, which were designated as HZ0512, HZ0527, HZ0714, HZ0723, HZ0726, HZ0811, HZ0815, and HN0403. The nucleotide homology among these strains ranged from 99.9% to 100%. There are two major categories of waterfowl parvoviruses, namely goose parvovirus (GPV) and Muscovy duck parvovirus. The eight strains, along with other NGPVs, belong to GPV.The eight strains showed a 92.5% -98.9% nucleotide homology with the classical GPV, while a 96.0% -99.9% homology with NGPV. Therefore, it can be deduced that there have been no major mutations of NGPV in Shandong and Henan provinces in recent years. Additionally, this study lays a theoretical foundation for further studying the genetic evolution and pathogenicity of NGPV, thereby facilitating the prevention and control of NGPV.